The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18794/aams/108959
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and ex vivo impact of nutritional xenobiotics – acrylamide and sodium nitrates – on plasma antioxidant properties

Abstract: INTRODUCTION: The thiol (SH) groups present in human blood plasma play an important role in the oxidative/antioxidative homeostasis of the organism. They are susceptible to the adverse actions of different exo-and endogenous factors. Chronic exposure to different xenobiotics, e.g. nitrogen-containing compounds commonly occurring in food, is especially important. The aim of this study was to investigate the effect of acrylamide (ACR) and sodium nitrates (SN)-(V) and (III)-on the plasma antioxidant properties, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The contribution of different food groups to nitrates and acrylamide intake in the examined student group stays in alignment with other studies and the authors' earlier examination [26]. Jackson et al [36] indicated vegetables (mainly lettuce and spinach) as the main source of nitrates in the group of Australian women, and the average intake of nitrates in the diet was estimated as 65-70 mg/day [39].…”
Section: The Nitrates and Acrylamide And Redox Status O R I G I N A L...supporting
confidence: 83%
See 1 more Smart Citation
“…The contribution of different food groups to nitrates and acrylamide intake in the examined student group stays in alignment with other studies and the authors' earlier examination [26]. Jackson et al [36] indicated vegetables (mainly lettuce and spinach) as the main source of nitrates in the group of Australian women, and the average intake of nitrates in the diet was estimated as 65-70 mg/day [39].…”
Section: The Nitrates and Acrylamide And Redox Status O R I G I N A L...supporting
confidence: 83%
“…The data collected using sFFQ allowed for assessment of current dietary exposure to nitrogen-containing food in all 151 participants of the study. For the assessment of value of daily intake of nitrates (DIN) and daily intake of acrylamide (DIA), the data derived from sFFQ were analyzed and appropriate formulas were applied to calculate DIN and DIA, as described earlier [26].…”
Section: The Nitrates and Acrylamide And Redox Status O R I G I N A L...mentioning
confidence: 99%